Intonation in European and Brazilian Portuguese - Frota, Sónia (2016)
This chapter describes the intonation system of Portuguese, concentrating on the analysis of the three main functions of intonation: demarcation, highlighting, and distinction of utterance types. It is based on the description of a single variety: the Lisbon variety for European Portuguese (EP), and the Rio de Janeiro variety for Brazilian Portuguese (BP). The chapter describes the language-particular preferences in intonational grouping that characterize European and Brazilian Portuguese, the size of intonational phrases, the distribution of tonal events within the intonational phrase and the ways in which intonational boundaries are realized. The chapter describes the intonation of two major types of questions: wh-questions and yes-no questions, as types of pragmatically neutral information-seeking questions. It is concerned with the intonation of wh-questions with the question word in sentence initial position. Finally, the chapter presents a typological look at the intonation of Portuguese within the Romance space.